Utopian Thinking in Law, Politics, Architecture and Technology Hope in a Hopeless World (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This innovative book explores the role of utopian thinking in law and politics, including alternative forms of social engineering, such as technology and architecture. Building on Levitas' Utopia as Method, the topic of utopia is addressed within the book from a multidisciplinary perspective.